Abstract from the log of William Tucker - Tucker, William, active 1844-1883.
Personal log kept by Tucker on various Atlantic voyages. Entries are brief and primarily numerical.
Handwritten transcript.
Ship captain.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Logbooks -- 19th century; Atlantic Ocean -- Description and travel; Ship captains